Company Size and Corporate Governance on Sustainability Reporting Disclosure: Moderating Role of Capital Structure - Sandy Arief; Ahmad Fadhly Arham; Hesti Susiloweni (Faculty of Economics, Universitas Negeri Indonesia,Indonesia, 2025)
This study aims to analyze the factors influencing the disclosure of sustainability reports in manufacturing sector companies listed on the Indonesia Stock Exchange. This study examined 174 samples of manufacturing companies. The research method employed a quantitative approach, and the data were analyzed using descriptive statistical analysis, inferential statistical tests, and Moderated Regression Analysis (MRA) tests. The results of this study indicate that the company size and corporate governance variables have a positive and significant influence on the disclosure of sustainability reports. In contrast, the model structure variable has no effect in moderating. These findings have implications for company management and stakeholders in enhancing transparency and corporate sustainability practices.